One step to synthesis (rGO/Ni NPs) nanocomposite and using to adsorption dyes from aqueous solution. (2019) - Al-Nafiey, Amer; Al-Mamoori, Mohammed H.K.; Alshrefi, Saif Mohammed; shakir, Ali K.; Ahmed, Rafea Tuama
Abstract: Nickel oxide nanoparticles (NiO NPs) were decorated on reduced graphene oxide via simples and easy reduction of graphene oxide and nickel salt in a single step reaction. By using some analytical techniques as well as, UV-vis spectrophotometry, scanning electron microscopy (SEM), energy dispersive X-ray (EDX) spectroscopy and Fourier-transform infrared (FTIR) spectroscopy, has been characterized the nanocomposite (rGO/NiO NPs). The nanocomposite (rGO/NiO NPs) has been found more suitable to obtain complete removal around 4 min when used as dyes adsorption. The nanocomposite (rGO/NiO NPs) is better than other graphene-based adsorbents with respect to the performance.